Development of Diorama Learning Media for Fourth Grade Elementary School - Lisa Sidyawati; Riris Masruroh; Intanta Erlianungka Siregar (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2021)
Learning media is a tool or intermediary that facilitates teaching and learning process and communication between teachers and students. This research is development research that aims to produce a diorama learning media about the rice field ecosystem food chain that is effective, practical and fun. The subjects of this study were 47 fourth graders from a public elementary school in Donowarih, East Java. This study concludes that the use of media in the learning process have impacts on teachers, students and the learning process in the classroom. In designing learning media, several steps must be considered, namely; media must be designed as simple as possible so that students are clear and easy to understand, media must be designed according to the subjects taught, media design is not too complicated and confuse children, the design of the media should use simple and easily available materials, but should not reduce the meaning and function of the media itself, and media can be designed in the form of models, pictures, structured charts, etc, but the materials are cheap and easy to get, so the teacher will have no trouble designing problematic media. Further researchers can use and develop this research and examine more sources and references.